Critical analysis on the role of mosque as an educational institution within the contemporary Muslim society in Malaysia - Lee, Cai Yin; Utaberta, Nangkula; Ismail, Nor Atiah; Mohd Ariffin, Noor Fazamimah; Mohd Yunos, Mohd Yazid; Ismail, Sumarni (AENSI Publisher, 2015)
Mosque is a significant institution since the time of Prophet Muhammad (pbuh) The mosque not only plays a comprehensive role as a place of worship, community and social center but it also is an important place for learning. Unfortunately, the development of contemporary human civilization has made the role of mosque as education center to be taken over by different secular institutions. The purpose of this paper is to discuss the development of mosque as an educational center. This paper uses the method of literature survey on two different mosques in Malaysia. Thus, it aims to improve the understanding on the role of mosque as educational center in modern Malaysian society.